Potensi Bakteri Pereduksi Sulfat dan Jenis Bahan Organik dalam Pengolahan Air Asam Tambang menggunakan System Constructed Wetland Tanaman akar Wangi (Vetiveria zizanioides L) - Pujawati Suryatmana; Apong Sandrawati; Ikrar Nusantara Putra; Nadia N. Kamaluddin (Fakultas Pertanian Universitas Padjadjaran, 2020)
Acid mine drainage (AMD) is a waste product from coal mining process. Acidic waste will impose a serious environmental issue such as organism annihilation and destruction of environmental ecosystem. Proper AMD management is required in order to restore polluted water to the proper standard condition. The Constructed Wetland system with Akar Wangi (Vetiveria zizanioides L.) and various organic growth medium compositions and sulphate-reducing bacteria and the composition of the media for several types of organic matter with sulfate-reducing bacteria (SRB) inoculation as stimulant was deemed a promising solution. This study was designed in randomized block design (RBD) consisted of nine treatments with three replicates. The treatments were: (A) = without organic matter and without SRB inoculation (control), (B) = 100% compost, (C) = 100% sawdust, (D) = 50% compost + 50% sawdust, (E ) = no organic matter + SRB inoculation (105 MPN ml-1), (F) = 100% compost + SRB inoculation, (G) = 100% sawdust + SRB inoculation, H = 50% compost + 50% sawdust + SRB inoculation, I = 75% compost + 25% sawdust + SRB inoculation. Results showed that 100% compost and SRB application increased polluted water pH. Application of 100% sawdust with or without SRB inoculation gave the highest reduction in sulfate content. SRB also has the potential to increase the height of Akar Wangi plant.